A Successful Limb-Sparing Approach in Synovial Sarcoma of The Foot: A Case Report - Triatmoko, Sara Ester; Andinata, Bob; Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Siburian, Elida Sari; Hidayat, Andika Prasdipta; Jonathan, Elisa; Sudarman, Jesica Putri (Jurnal Plastik Rekonstruksi, 2025)
Synovial sarcoma, although rare, is commonly diagnosed in patients under 20 years of age. This case presents the case of a 21-year-old female with synovial sarcoma affecting the 1st to 3rd metatarsal and tarsal bones. She underwent extensive tumor resection, followed by fibula free flap. The fibula was reconstructed into an L-shape to provide structural support. A bypass was performed because of compromised blood flow to the first digit, but the digit failed. Skin necrosis occurred after tumor dissection, necessitating a second reconstruction with an anterolateral thigh flap (ALT) after six weeks. At the years follow-up, the reconstruction was stable, and radiation therapy further improved the outcomes. The patient’s gait was satisfactory, with special shoes for weight bearing. This case demonstrates the potential of limb-sparing surgery with free fibula flaps for synovial sarcoma resection, which offers promising functional and psychological benefits.